Hyaluronic acid suppresses age related skin changes - S. A. Larkina; N. N. Oleynik; R. S. Vastyanov (Kazimierz Wielki University, 2017)
Functioning of the skin with age leads to its changes under which the condition of the dermis fibers deteriorates, which affects the appearance of the person and causes a number of consecutive pathological processes in the skin deeper layers. The development of methods for the prevention and treatment of age-related involuntary changes in the skin, enhancement of repair processes in its various layers is relevant and has a scientific and practical significance. Morphological studies of rabbits skin after the exogenous hyaluronic acid (HA) administration in various concentrations were performed. Studies have shown that when HA various concentrations are injected intradermally into rabbits, the increase in the formation of connective tissue fibers in the dermis is manifested with an increase of HA concentration. An increase in the HA concentration in the compounds promotes an increase in the degree of compaction of the dermis of rabbits. Lower HA concentration (1.4% and 2%) after single administration causes stimulation of the processes inside the skin at earlier time (2 weeks), and a concentration of 4% - is more active at a later time (8 weeks). We can assume a connection between the HA concentration and the time of the manifestation of the most pronounced morphological changes in the skin. It is likely that the stimulating effect of HA is manifested when the optimal physiological concentration is reached. The obtained data are in favor of further studies of the influence of the concentration of exogenous HA on the processes of skin biorevitalization.